Evaluation of Atrial Conduction Times and Epicardial Adipose Tissue Thickness in Patients with Ankylosing Spondylitis - (:unkn) unknown (ISTANBUL TRAINING & RESEARCH HOSPITAL, 2020)
Introduction: In this study, we aimed to evaluate whether atrial electromechanical delay (EMD) and epicardial adipose tissue (EAT) thickness differed between ankylosing spondylitis (AS) patients and healthy subjects. Methods: This prospective, cross-sectional study included 43 consecutive AS patients followed up in the Physical Medicine and Rehabilitation Department of the University of Health Sciences Turkey, Istanbul Training and Research Hospital, between June 2019 and January 2020. The control group consisted of 42 age-and gender-matched healthy participants. The PA atrial EMD was accepted as the beginning of the P wave on the electrocardiograph and the begining of late diastolic wave (Am wave) on the tissue Doppler obtained by transthoracic echocardiography, and all EMD parameters, including lateral mitral annulus (lateral PA), septa! mitral annulus (septa) PA) and right ventricular tricuspid annulus (tricuspid PA), were calculated. The thickness of EAT was obtained from the thickest part of the right ventricular free wall at the end of diastole in the parasternal long axis window. Results: In AS patients, tissue Doppler measurements of PA lateral, PA septal and PA tricuspid were longer than the measurements in the control group. In addition, EAT thickness was significantly higher in AS patients than in the control group. There was a moderate correlation between interatrial EMD and C-reactive protein (r=0.445, p<0.001) and EAT thickness (r=0.451, p<0.001). Conclusion: In this study, interatrial EMD and intraatrial EMD were significantly higher in AS patients. In addition, the thickness of EAD was significantly greater in patients with AS. These findings suggest a higher tendency toward coronary artery disease and atrial fibrillation in patients with AS.
Keywords: Ankylosing spondylitis; electromechanical delay; epicardial adipose tissue; atrial fibrillation; PERICARDIAL FAT; FIBRILLATION